THE GALOMBANG OF INDONESIA: A CULTURAL DANCE TRANSITION IN PROCESS: GALOMBANG INDONESIA: PROSES TRANSISI TARIAN BUDAYA - Adnan, Nerosti; Bujang, Rahmah; a/l Edo, Juli (Jurnal Pengajian Melayu (JOMAS), 2013)
The article is based on research towards realizing the first writer’s PhD thesis on the subject of Tarian Galombang Masyarakat Minangkabau: Kajian Kes di Kota Padang (the Changing Galombang Dance of Minangkabau: Case of Kota Padang). The dance form is traditionally performed as an expressive medium in the investiture of a customary leader in Minangkabau society, as in respecting a Penghulu, a leader’s family wedding, accompanying the act of customary bath rites, and alek nagari. Its execution involves upto 20 or more men performing the silat in a style referred to as silek galombang. This article investigates the changes in the dance choreography and function which seem to be bias to the succession into the form as medium for injecting interest in the tourism industri for the area. One very pertinent change is the inclusión of female dancers leading to process of changes in its creative form per movement, floor pattern, props as well as costumery and accessorizings. Yet the customary aesthetic symbolism of the dance form has been maintained in the process strengthening its position of cultural heritage. This paper seeks to enlighten readers on the textual and contextual impact of the changes that has occurred in the dance form pursuing the phenomenon in accordance with theory propounded by Maquet (1980) of art by destination and by metamorphosis and Soerdarsono (1994) who has explained in general the concept of art form for tourism as minimum, not original, varied, non sacred and short in time execution of its performance. Keywords: Galombang, Minangkabau, tourism industry. Artikel ini adalah merupakan petikan dari Tesis Doktor Falsafah penulis pertama yang bertajuk: Tari Galombang di Era Perubahan Sosial Budaya Masyarakat Minangkabau: Kajian Kes di Kota Padang. Tari Galombang merupakan tari tradisional Minangkabau yang dipersembahkan sebagai tarian penyambutan tetamu dalam pelbagai upacara adat Minangkabau, seperti penobatan Penghulu (kepala suku), majlis perkahwinan, turun mandi, dan alek nagari. Iaitu ditarikan oleh sekitar 20 lelaki dengan bergaya pencak silat yang disebut juga silek galombang. Artikel menyiasat perubahan yang telah berlaku dalam koreografi tari tersebut dengan berlakunya fungsi terkini yang menekankan kepada bentuk itu sebagai satu daya tarikan pelancongan di Kota Padang. Perubahan yang amat ketara ialah penglibatan kaum wanita yang turut melibatkan proses perubahan kreativiti bentuk tarinya pada gerak, pola lantai, prop, kostum dan aksesori. Namun disebalik kreativiti baru tari galombang masih tetap menampilkan simbol-simbol estetika adat Minangkabau sehingga ianya kekal sebagai warisan leluhur budaya Minangkabau. Perubahan tari Galombang dari segi tekstual dan kontekstual merupakan impak daripada dunia pelancongan sesuai teori Maquet (1980) dan Soerdarsono (1994). Maquet mengkategorikan 2 bentuk produksi seni iaitu’ art by destination’ dan ‘art by metamorfosis’. ‘Art by destination’ adalah tari Galombang asli, dan ‘art by metamorfosis’ adalah tari Galombang yang sudah berubah. Soedarsono pula menghuraikan konsep seni pelancongan adalah: bentuk mini, bentuk tiruan, penuh variasi, tidak sakral, dan singkat masa pelaksanaannya. Artikel akan mengenalpasti bentuk seperti yang dinyatakan oleh pendapat tersebut pada tari Galombang yang berkembang di Kota Padang. Kata kunci: Galombang, Minangkabau, industri pelancongan